2019
DOI: 10.21203/rs.2.10457/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional status of tuberculosis patients, a comparative cross-sectional study

Abstract: Background Each year, more than 13.7 million people became an active case of tuberculosis and more than 1.5 million cases of tuberculosis patient will die. The association between tuberculosis and malnutrition is bi-directional, tuberculosis leads the patient to malnutrition, and malnutrition increases the risk of developing active tuberculosis by 6 to 10 times higher. Improving the nutrition of individual greatly reduces tuberculosis. The objectives of this study were to assess the nutritional status and det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(18,20 ) This finding is consistent with other studies where individuals who malnourished had a higher risk of acquiring TB infection compared to those who not malnourished. (2,(17)(18)(19) In the multivariate analysis we found that socioeconomic status was not related to TB incidence. However, in the bivariate analysis socioeconomic status was related to the incidence of TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(18,20 ) This finding is consistent with other studies where individuals who malnourished had a higher risk of acquiring TB infection compared to those who not malnourished. (2,(17)(18)(19) In the multivariate analysis we found that socioeconomic status was not related to TB incidence. However, in the bivariate analysis socioeconomic status was related to the incidence of TB.…”
Section: Discussionmentioning
confidence: 99%
“…TB predisposes the patient to malnutrition and malnutrition increases the vulnerability of developing the disease. (18,19) Epidemiological studies have shown that malnutrition affects genetic expression and impaired immune response, which are predisposing factors for tuberculosis progression. (2,16,18) Malnutrition is one of important risk factors for TB because it profoundly affects cell-mediated immunity (CMI).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in the United States, Indonesia, India, Gambia and Tanzania have confirmed that anaemia is particularly common in patients with TB (Boloor et al 2012;Cegielski et al 2012;Isanaka et al 2012;Karyadi et al 2000;Minchella et al 2015) predominantly because of anaemia of inflammation (also known as anaemia of chronic disease) (Minchella et al 2015), which may have been the case in the current study, where this phenomenon was frequently reported. Some studies have reported a lower prevalence of iron deficiency in patients with TB compared with control groups (Feleke, Feleke & Biadglegne 2019;Friis et al 2009;Van Lettow et al 2005). The incidence of an iron deficiency in patients with TB is most likely to vary across populations because of contextual factors, such as dietary intake and prevalence of other infections (Isanaka et al 2012).…”
Section: Discussionmentioning
confidence: 99%